Policies of Developing Publishing Activities in the Current Context of Vietnam - Le, Dang Thanh; Do, Do Thanh; Tuan, Luc Anh; Hung, Cao Thanh; Le Thu, Nguyen Thi (Journal of Posthumanism, 2025)
This study aims to understand the current state of publishing activities in Ho Chi Minh City, Vietnam, as well as to identify future development trends. The research seeks to recommend necessary policies to further promote the growth of these activities within the city. The study was carried out by analyzing and summarizing secondary documents, and conducting a sociological survey. This survey involved a questionnaire distributed to 186 leaders and employees from publishing companies, businesses, and individuals involved in the fields of printing, publishing, and distribution, along with 533 readers. The research findings highlight both the achievements and limitations of current publishing activities. It outlines five future development trends and proposes eight essential policies aimed at enhancing the publishing landscape in Ho Chi Minh City.